2003
DOI: 10.3998/ark.5550190.0004.a13
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective approach to the asymmetric synthesis of (6R)-hydroxymethyl-5,6-dihydro-2H-pyran-2-one. A formal synthesis of (R)-argentilactone and total synthesis of (R)-goniothalamin

Abstract: The asymmetric synthesis of the (6R)-hydroxymethyl-5,6-dihydro-2H-pyran-2-one, a key intermediate in the formal synthesis of (R)-argentilactone, and the total synthesis of (R)-goniothalamin are described. Our aproach involved the Lemieux-Johnson oxidative cleavage, enantioselective Keck allylation, ring-closing metathesis and Wittig olefination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Due to its diverse pharmacological properties, GTN gained huge interest from researchers because several successful approaches have been adopted for its synthesis [ 50 54 ]. The absolute configuration in the pyran-2-one moiety has generally been secured from chiral starting material, asymmetric allylboration of aldehydes with β -allyldiisopinocampehylborane [ 50 , 55 , 56 ], or through asymmetric reduction using enzymes or microorganisms [ 51 , 53 , 54 , 57 61 ]. De Fátima and Pilli [ 51 ] reported the syntheses of GTN via catalytic asymmetric allylation of α-benzyloxyacetaldehyde, followed by ring-closing metathesis and Wittig olefination, and via catalytic asymmetric allylation of trans-cinnamaldehyde, followed by ring-closing metathesis [ 62 ].…”
Section: Synthesis Of Goniothalaminmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to its diverse pharmacological properties, GTN gained huge interest from researchers because several successful approaches have been adopted for its synthesis [ 50 54 ]. The absolute configuration in the pyran-2-one moiety has generally been secured from chiral starting material, asymmetric allylboration of aldehydes with β -allyldiisopinocampehylborane [ 50 , 55 , 56 ], or through asymmetric reduction using enzymes or microorganisms [ 51 , 53 , 54 , 57 61 ]. De Fátima and Pilli [ 51 ] reported the syntheses of GTN via catalytic asymmetric allylation of α-benzyloxyacetaldehyde, followed by ring-closing metathesis and Wittig olefination, and via catalytic asymmetric allylation of trans-cinnamaldehyde, followed by ring-closing metathesis [ 62 ].…”
Section: Synthesis Of Goniothalaminmentioning
confidence: 99%
“…The absolute configuration in the pyran-2-one moiety has generally been secured from chiral starting material, asymmetric allylboration of aldehydes with β -allyldiisopinocampehylborane [ 50 , 55 , 56 ], or through asymmetric reduction using enzymes or microorganisms [ 51 , 53 , 54 , 57 61 ]. De Fátima and Pilli [ 51 ] reported the syntheses of GTN via catalytic asymmetric allylation of α-benzyloxyacetaldehyde, followed by ring-closing metathesis and Wittig olefination, and via catalytic asymmetric allylation of trans-cinnamaldehyde, followed by ring-closing metathesis [ 62 ]. Gruttadauria et al [ 54 ] along with coworkers reported that the high-yielding three-step synthesis of GTN involves an enzymatic kinetic resolution in the presence of vinyl acrylate followed by ring-closing metathesis [ 54 ].…”
Section: Synthesis Of Goniothalaminmentioning
confidence: 99%
“…Subsequent RCM of 2 using the catalyst 5 produced the polycyclic ether 4 in a high yield. This methodology was applied to the total synthesis of gambierol. 13c,d Recent reports on the total synthesis of heterocyclic natural products using RCM are summarized in Table . 13c,d,
3
4
5
6
…”
Section: 1 Ring-closing Metathesis For Total Synthesismentioning
confidence: 99%
“…Several batch strategies have been proposed for the asymmetric synthesis of goniothalamin ( 1 ). , For example, Singh and co-workers employed an auxiliary-controlled asymmetric aldol reaction for the construction of an enantiopure homoallylic alcohol intermediate . Asymmetric allylboration was described by Brown and co-workers, achieving homoallylic alcohol intermediate ( 12 ) in 92–97% enantiomeric excess (ee) .…”
Section: Resultsmentioning
confidence: 99%